The new injury severity score underestimates true injury severity in a resource-constrained setting - Smitha Bhaumik; Krithika Suresh; Hendrick Lategan; Elmin Steyn; Nee-Kofi Mould-Millman (African Journal of Emergency Medicine, 2024)
Background: The new injury severity score (NISS) is widely used within trauma outcomes research. NISS is a composite anatomic severity score derived from the Abbreviated Injury Scale (AIS) protocol. It has been postulated that NISS underestimates trauma severity in resource-constrained settings, which may contribute to erroneous research conclusions. We formally compare NISS to an expert panel's assessment of injury severity in South Africa. Methods: This was a retrospective chart review of adult trauma patients seen in a tertiary trauma center. Randomly selected medical records were reviewed by an AIS-certified rater who assigned an AIS severity score for each anatomic injury. A panel of five South African trauma experts independently reviewed the same charts and assigned consensus severity scores using a similar scale for comparability. NISS was calculated as the sum of the squares of the three highest assigned severity scores per patient. The difference in average NISS between rater and expert panel was assessed using a multivariable linear mixed effects regression adjusted for patient demographics, injury mechanism and type. Results: Of 49 patients with 190 anatomic injuries, the majority were male (n = 38), the average age was 36 (range 18–80), with either a penetrating (n = 23) or blunt (n = 26) injury, resulting in 4 deaths. Mean NISS was 16 (SD 15) for the AIS rater compared to 28 (SD 20) for the expert panel. Adjusted for potential confounders, AIS rater NISS was on average 11 points (95 % CI: 7, 15) lower than the expert panel NISS (p < 0.001). Injury type was an effect modifier, with the difference between the AIS rater and expert panel being greater in penetrating versus blunt injury (16 vs. 7; p = 0.04). Crush injury was not well-captured by AIS protocol. Conclusion: NISS may under-estimate the ‘true’ injury severity in a middle-income country trauma hospital, particularly for patients with penetrating injury.